2018
DOI: 10.1074/jbc.ra118.003560
|View full text |Cite
|
Sign up to set email alerts
|

The Ras-like GTPase Rem2 is a potent inhibitor of calcium/calmodulin-dependent kinase II activity

Abstract: Ca/calmodulin-dependent protein kinase II (CaMKII) is a well-characterized, abundant protein kinase that regulates a diverse set of functions in a tissue-specific manner. For example, in heart muscle, CaMKII regulates Ca homeostasis, whereas in neurons, CaMKII regulates activity-dependent dendritic remodeling and long-term potentiation (LTP), a neurobiological correlate of learning and memory. Previously, we identified the GTPase Rem2 as a critical regulator of dendrite branching and homeostatic plasticity in … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
38
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(41 citation statements)
references
References 54 publications
3
38
0
Order By: Relevance
“…This is consistent with the many alterations we observe in our past and current studies of Rem2 deletion [51, 54, 55, 67, 7679]. Compellingly, the ability for Rem2 to inhibit CaMKII catalytic activity has already been linked to regulation of dendritic complexity [79]. We propose a model in which direct inhibition of CaMKII by Rem2 promotes morphological stability, the loss of which results in cascading instability of the dendritic arbor.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…This is consistent with the many alterations we observe in our past and current studies of Rem2 deletion [51, 54, 55, 67, 7679]. Compellingly, the ability for Rem2 to inhibit CaMKII catalytic activity has already been linked to regulation of dendritic complexity [79]. We propose a model in which direct inhibition of CaMKII by Rem2 promotes morphological stability, the loss of which results in cascading instability of the dendritic arbor.…”
Section: Discussionsupporting
confidence: 89%
“…Likewise, loss of such inhibition leading to increased CaMKII catalytic activity, such as by Rem2 deletion, could lead to widespread changes in cellular structure and function. This is consistent with the many alterations we observe in our past and current studies of Rem2 deletion [51, 54, 55, 67, 7679]. Compellingly, the ability for Rem2 to inhibit CaMKII catalytic activity has already been linked to regulation of dendritic complexity [79].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The assay has been used previously by us and other groups to monitor the activity of purified CaMKII in vitro. 6,12 We found that addition of CaMKIIα to the reaction mixture led to a fast consumption of ATP due to the phosphorylation of the 15 amino acid peptide substrate syntide-2 by CaMKII ( Figure 1B,C). When the experiment was repeated in the presence of 500 nM wtNme1, a strong increase in total ATP consumption was detected.…”
Section: Graphical Abstractmentioning
confidence: 95%